Testing a Model of Domestic Abuse Against Elder Women and Barriers to Help-Seeking in Miami-Dade County, Florida, 2006 - Newman, Frederrick ([Verlag nicht ermittelbar], 2014)
This study sought to understand perceived barriers to help-seeking for female victims of domestic abuse age 50 years and older (by a spouse, partner, adult child, grandchild, other relative or close friend) relative to the perceived barriers for women in the same age group who are not victims of such abuse. Additionally, the study explored the impact of key demographic variables of race and ethnicity, relationship to the presumed abuser, and age at the time of the survey on perceived barriers of victims. To address these research questions this study tested an empirical model that described relevant factors regarding perceived barriers to help-seeking and explored if and how this model changed based on the identified variables. Study participants represented a community sample of females age 50 years and older interested in participating in research regarding conflict in close personal relationships experienced by women in this target age range. Specific aims for the project were intended to lead to increased knowledge regarding perceived barriers to help-seeking among older women and, in particular, to develop a basis for describing (a) if and how these perceived barriers were unique to domestic abuse victims relative to non-victims in this age group and (b) how they varied based on selected variables.